Coconut Fiber Export Competitiveness: Implementation of Corporate Advantages Business Strategy - Lestari, Dian Trianita; Setiawan, Utomo Putro; Abdullah, Muhammad Zein (Dauliyah: Journal of Islam and International Affairs, 2023)
This research aims to analyze the factors that determine the coconut fiber export competitiveness of PT. Weida Indocoir Prima by using Porter's theory of competitive advantage. This research uses qualitative methods with data collection techniques through interviews and documentation. The results show that there are three factors that determine the export competitiveness of PT. Weida Indocoir Prima, namely first, factor condition which includes workers who receive direct training from China, abundant natural resources/coconut fibers in Southeast Sulawesi Province and adequate infrastructure with the construction of the Kendari New Port which facilitates direct exports to destination countries, secondly, the demand condition from China which requests a large enough quantity of coconut fiber, and thirdly, support from the Southeast Sulawesi government represented by the Industry and Trade Office by providing guidance technical marketing, efforts to diversify export market products as well as carrying out administrative functions in the form of making a Certificate of Origin document. From the results of this research, it can be concluded that the export competitiveness of coconut fiber by PT. Weida Indocoir Prima is quite good, while the export share needs to be expanded beyond China.